Pengembangan Lembar Kerja Peserta Didik (LKPD) Berbasis Problem Solving pada Materi Sistem Ekskresi Manusia Kelas XI SMA/MA - City Qurnia Sari Pohan; Kartika Manalu; Reflina (Jurnal Dirosah Islamiyah, 2024)
This examination aims to determine the validity, reasonableness and appropriateness of critical thinking prepared by students' worksheets regarding the human excretory framework material for class XI senior high schools in educational experiences. This exam uses Innovative work (RnD) research techniques with a 4D model (Define, Design, Development, and Dissemination). which is adjusted to 3D (Define, Design, and Development). Exploratory instruments use consent forms, surveys and critical thinking skills tests. The consequences of this exploration show that the critical thinking-based student worksheet that has been created is valid and suitable to be applied with a level of 83.3% (material experts) with the "Very Substantial" rule and 81.9% (media experts) with the "Very Substantial" rule. Very large". The student worksheet was also declared suitable based on the poll of educators and students obtained, namely 93% with the "Very Great" model and 87% (students) with the "Very Valid" standard. The students' worksheet was also declared suitable based on the N-Gainscore results of 0.61 with the "Compelling" model. Looking at the results of the exploration, the critical thinking students' worksheets on the human excretory framework material for class in use. The student worksheets created can expand student learning practice and educators can involve student worksheets as display material in educational experiences.